Performance of vertically mounted bifacial photovoltaics under the physical influence of low-rise residential environment in high-latitude locations - Viriyaroj, Bergpob; Jouttijärvi, Sami; Jänkälä, Matti; Miettunen, Kati (Frontiers in Built Environment, 2024)
This study focuses on finding suitable installation sites for vertical bifacial photovoltaic (VBPV) panels in urban low-rise neighborhoods at high latitudes. The power production of east-west-oriented VBPV systems matches well with domestic electricity consumption profiles, increasing the selfconsumption of PV electricity. Furthermore, PV electricity adds economic value by avoiding transmission fees and taxes. These systems are especially beneficial in high-latitude locations characterized by a low solar elevation angle. However, these low angles expose VBPV panels to a high risk of shading losses from their surroundings, and it is unknown how much shading limits the number of suitable installation sites. Here, environmental shading on VBPV panels is quantified for three low-rise residential neighborhoods in Helsinki, a high-latitude location, by comparing the specific yields (annual electricity production per kilowatt peak) of VBPV and monofacial PV (MPV) systems. The results showed that unshaded VBPV systems have a higher specific yield than their MPV counterparts. However, in densely built neighborhoods with tall trees, the lack of suitable installation sites for VBPV panels severely limits the peak power of these systems. Roof ridge VBPVs usually yield high production, while façade-and ground-mounted systems lose between 30% and 70% compared to roof ridge VBPV systems depending on their installation locations. Southoriented MPVs perform better than VBPVs on north-south-facing roofs, both in terms of specific yield and total annual production. Conversely, VBPVs installed on the ridges of unshaded roofs aligned closely with the north-south axis outperform MPVs on east-and west-facing roofs by 20-30%.